Pemilihan Supplier dan Alokasi Order Asam Jawa Dengan Menggunakan Metode Fuzzy AHP Dan Goal Programing - Mulasi, Sebro (Jurnal Teknik Industri, 2015)
Supplier selection process was become important consideration to improve the efficiency of procurement department because the raw material cost could reach 70% of product cost.  The supplier selection process was multi-criteria problem involving qualitative and quantitative factors. The company often experienced shortage of  good quality tamarind  with a cheap price which companies often reject order from customers. Therefore the company should make a selective supplier selection and allocation of orders for optimum results by considering both qualitative and quantitative factors that can minimize the cost of purchase, maximizing the weight of suppliers and minimize the total defect order. This research will integrate supplier weight from Fuzzy Analytic Hierarchy Process and Goal Programming model for the final decision of supplier selection and allocation of orders. By running goal programming model give solution better than order allocation current model where it could reduce total cost of purchasing at Rp 130.000.000 to Rp 127.700.000 and reduce total of defect order at 4%  to 0,87%.